Musculoskeletal manifestations of sickle cell disease - Pacheco, María (1997)
Musculoskeletal manifestations are common in the hemoglobinopathies. Two cases of homozygous sickle cell disease (hemoglobin SS) with osteoarticular manifestations associated to hemolytic crises are described. A 22-year-old woman with avascular necrosis of the right femoral head, and a 21-year-old man with joint effusion in both knees.